The Intelligent Organization and Knowledge Management Enablement : From Overbooking Barriers to Building Cognitive Capabilities - Hamida, Zouaoui (Journal of Ecohumanism, 2025)
This article aims to analyze the role of the intelligent organization in enabling knowledge management within institutions. It focuses on how to overcome organizational and cognitive obstacles that hinder the effectiveness of knowledge management, and how to shift towards building advanced knowledge capabilities.The study draws on a theoretical framework that integrates the characteristics of the intelligent organization—such as organizational learning, flexible structure, and effective communication—with the stages of knowledge management, based on recent literature and relevant conceptual models.The research also explores institutional factors that weak knowledge management practices, such as resistance to change, weak participatory culture, and insufficient technological infrastructure. It shows how the intelligent organization can overcome these challenges by adopting smart practices that enhance the organization's ability to acquire, generate, and apply knowledge effectively.The study concludes that the features of the intelligent organization serve as a key strategic enabler for knowledge management. Furthermore, adopting organizational intelligence significantly contributes to reducing knowledge gaps and activating intellectual capital, thereby strengthening competitiveness and future readiness in contemporary work environments.